2020
DOI: 10.1002/jia2.25536
|View full text |Cite
|
Sign up to set email alerts
|

Influences on willingness to use vaginal or oral HIV PrEP during pregnancy and breastfeeding in Africa: the multisite MAMMA study

Abstract: IntroductionWomen in sub‐Saharan Africa spend a substantial portion of their reproductive lives pregnant and/or breastfeeding (P/BF), yet they have limited options to prevent HIV during these maternal stages. In preparation for phase 3b prevention trials in P/BF women, we explored attitudes about using a vaginal ring or oral pills for pre‐exposure prophylaxis (PrEP), perceptions of HIV risk during P/BF and key influences on future PrEP use.MethodsIn 2018, we conducted 16 single‐sex focus group discussions (FGD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Pseudonyms were used to represent different participants in each FGD transcript. Additional details about study procedures can be found in van der Straten et al (2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudonyms were used to represent different participants in each FGD transcript. Additional details about study procedures can be found in van der Straten et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…The data were analysed using framework analysis, a qualitative method for applied research (Srivastava & Thomson, 2009). A codebook of inductive and deductive codes (Data S1) was iteratively developed with staff from the study sites using a modified socio‐ecological framework as previously described (van der Straten et al, 2020). A team of five qualitative analysts, three of whom were involved throughout the study, coded the transcripts using Dedoose software v7.0.23 and maintaining ~80% intercoder reliability.…”
Section: Methodsmentioning
confidence: 99%
“…This is because pregnant women are routinely excluded from clinical trials because of ethical considerations and the fear of potential fetal harm. 3–5 …”
Section: Introductionmentioning
confidence: 99%
“…To address women’s vulnerability to HIV during pregnancy and breastfeeding, evaluating HIV prevention methods that can be initiated and used by the women themselves are important. This includes daily oral Pre- Exposure Prophylaxis (PrEP) [ 4 , 5 ] and monthly vaginal rings [ 6 , 7 ]. The Word Health Organisation recommends offering daily Truvada™ or emtricitabine(FTC) / tenofovir disoproxil fumarate (TDF) pills to women at considerable risk of HIV infection [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Primary findings indicated that there was consensus amongst men and women, that P/BF women are at higher risk of HIV due to their partners infidelity. Both women and men welcomed new methods of prevention [ 7 ]. Reported influences on future product use included safety considerations for the mother and child dyad; women having support from their partners, men being involved in the decision making process; women expressing the importance of having support from the wider family on decision to use PrEP methods, and endorsement of products by healthcare professionals [ 7 ].…”
Section: Introductionmentioning
confidence: 99%